La danza en la escuela y la formación de los profesores - Herminia María García Ruso (Universidad de La Rioja, 2013)
In Organic Law 1/1990 of 3rd October of the general arrangement of the educational system (LOGSE), the educational system includes the general regime education and the special regime education. Dance is included in the special regime as part of the artistic disciplines together with music, drama, the plastic arts and design. The aim of this article is to analyse the treatment given to Dance in the general regime. Thus, we will try to emphasize the inconsistency that exists between the areas of primary education, which will be obligatory and will have a global and integrated character, and the training of future teachers.